Mid-titer human convalescent plasma administration results in suboptimal prophylaxis against SARS-CoV-2 infection in rhesus macaques - Beddingfield, Brandon J.; Maness, Nicholas J.; Spencer, Skye; Rappaport, Jay; Aye, Pyone Pyone; Russell-Lodrigue, Kasi; Doyle-Meyers, Lara A.; Blair, Robert V.; Gao, HongMei; Montefiori, David; Roy, Chad J. (Frontiers in Immunology, 2023)
SARS-CoV-2 is a respiratory pathogen currently causing a worldwide pandemic, with resulting pathology of differing severity in humans, from mild illness to severe disease and death. The rhesus macaque model of COVID-19 was utilized to evaluate the added benefit of prophylactic administration of human post-SARS-CoV-2 infection convalescent plasma (CP) on disease progression and severity. A pharmacokinetic (PK) study using CP in rhesus monkeys preceded the challenge study and revealed the optimal time of tissue distribution for maximal effect. Thereafter, CP was administered prophylactically three days prior to mucosal SARS-CoV-2 viral challenge. Results show similar viral kinetics in mucosal sites over the course of infection independent of administration of CP or normal plasma, or historic controls with no plasma. No changes were noted upon necropsy via histopathology, although there were differences in levels of vRNA in tissues, with both normal and CP seemingly blunting viral loads. Results indicate that prophylactic administration with mid-titer CP is not effective in reducing disease severity of SARS-CoV-2 infection in the rhesus COVID-19 disease model.